A Preliminary Study Comparing Pre-service and In-service School Principals’ Self-Perception of Distributed Leadership Competencies in Relation to Teaching and Managerial Experience - Cebrián, Gisela; Moraleda, Álvaro; Galán-Casado, Diego; Andújar-Molina, Olvido (Frontiers in Psychology, 2022)
So far little are the studies that have focussed on exploring school principals’ self-conception of their distributed leadership competencies in relation to their managerial and teaching experience. To do so, an exploratory research was carried out with a sample of 163 pre-service and in-service school principals studying a Master’s programme in School Management, Innovation and Leadership at a Spanish University. Data were obtained by using an Ad hoc questionnaire of 7 units of competence and 5 proficiency levels for each unit, based on an existing rubric to analyse students’ self-conception of their development of leadership competencies. The findings of this preliminary study show statistically significant differences in the self-perception in all dimensions associated to Managerial Experience (ME) and Teaching Experience (TE) in schools. Study participants with ME showed statistically higher levels than those who had non-ME in four of seven dimensions: lead the school organisation, address the needs of the students, manage the organisation of the school organisation, and manage administrative work. Similar results were obtained in relation to TE versus non-TE were statistically significant differences are found in six dimensions: manage pedagogical and didactic resources, attend to the needs of students, manage didactic strategies, manage the organisation of the school organisation, manage the link between the school organisation and the community, and lead the school organisation. This study shows the importance of teaching and professional experience to acquire leadership competencies in education, therefore the school principal should also be a teacher. This preliminary study provides insights into the relevance of providing pre-service or in-service school principals with training and professional development programmes on sustainability distributed leadership that enable them to genuinely engage the school community, develop innovative pedagogies and lead the process of change toward building more sustainable schools.